A review of STEM education research in BRICS countries: an analysis of research trends - Fayzullina, Albina R.; Zulfugarzade, Teymur E.; Kondakchian, Nataliia A.; Aytuganova, Jhanna I.; Khvatova, Maria A.; Kelina, Kirena G. (Frontiers in Education, 2024)
Research has emphasized the importance of STEM for countries. Many studies have been conducted on STEM education research in countries worldwide. However, there is a lack of research on reviewing the research on STEM education in BRICS countries. Based on this rationale, this paper analyzes research patterns and trends related to STEM education in BRICS countries. The study examined 3,580 journal articles from 2014 to 2023 on STEM education in BRICS countries using the bibliometric analysis method, revealing a significant increase in research. The results showed that the number of published articles increased annually, and 85% were published after 2017. The top three journals publishing STEM studies were the Journal of Engineering Education Transformations, Sustainability, and the International Journal of Emerging Technologies in Learning. China had the highest number of articles on STEM education based on country affiliation, followed by South Africa, India, Brazil, and Russia. The authors’ authorship collaborations revealed that China had the most prominent connections compared to other countries. The keywords analysis revealed four research trends: (i) the effects of STEM education on learning outcomes, (ii) the impacts of instructional strategies in engineering education, (iii) gender differences in STEM education, and (iv) the use of artificial intelligence, project-based learning, and active learning. Based on the analyses, researchers suggest recommendations for future research.